2018
DOI: 10.1016/j.bjid.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Fatal case of donor-derived colistin-resistant carbapenemase-producing Klebsiella pneumoniae transmission in cardiac transplantation

Abstract: Herein we report a fatal case of donor-derived transmission of XDR-resistant carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) in cardiac transplantation. A 59-year-old male patient with non-obstructive hypertrophic cardiomyopathy underwent heart transplantation. On day 5 post-operation, blood cultures from the donor were positive for colistin-resistant carbapenemase-producing K. pneumoniae (ColR KPC-Kp) susceptible only to amikacin. Recipient blood cultures were also positive for ColR KPC-Kp with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…More specifically, Amdani et al reported on pediatric heart transplant recipients from blood culture‐positive donors showing there was no difference in survival or post‐transplant complications with these donors compared to donors with negative blood cultures. However, with the emergence of multi‐drug‐resistant (MDR) organisms, transmission from donor to recipient of these difficult‐to‐treat organisms has been reported in adult heart transplantation, although organs from donors with some MDR organisms including carbapenamase‐resistant Klebsiella pneumoniae have been safely used in at least one adult heart transplant recipient with targeted peri‐operative and post‐operative antimicrobial administration . To date, no pediatric reports using donors with MDR bacterial infections appear in the literature and donors with these organisms should be considered with caution focusing on the therapies available to treat a recipient should a donor‐derived infection develop.…”
Section: Donor Infectionsmentioning
confidence: 99%
“…More specifically, Amdani et al reported on pediatric heart transplant recipients from blood culture‐positive donors showing there was no difference in survival or post‐transplant complications with these donors compared to donors with negative blood cultures. However, with the emergence of multi‐drug‐resistant (MDR) organisms, transmission from donor to recipient of these difficult‐to‐treat organisms has been reported in adult heart transplantation, although organs from donors with some MDR organisms including carbapenamase‐resistant Klebsiella pneumoniae have been safely used in at least one adult heart transplant recipient with targeted peri‐operative and post‐operative antimicrobial administration . To date, no pediatric reports using donors with MDR bacterial infections appear in the literature and donors with these organisms should be considered with caution focusing on the therapies available to treat a recipient should a donor‐derived infection develop.…”
Section: Donor Infectionsmentioning
confidence: 99%
“…Overall, 28 studies were selected for fulltext review, and 21 studies met our inclusion criteria. For these 21 studies, three trials [33][34][35] were cohort or casecontrol studies, and 18 reports [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were case series or case reports. The flow diagram (Fig.…”
Section: Study Identificationmentioning
confidence: 99%
“…However, none of the organ recipients who received appropriate antibiotic therapy, defined as targeted therapy initiated within 7 days of transplantation and continued for at least 7 days, developed an infection with the resistant organism [56]. In the literature, there have been at least nine cases of reported CRE transmission from donor to organ recipient [54,57]. Rapid diagnosis and communication with the recipient's healthcare team can significantly impact empiric antibiotic regimens and mortality [54].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%